The role of empiric atypical antibiotic coverage in non-severe community-acquired pneumonia - Whitney Hartlage; Hannah Imlay; Emily S. Spivak (Antimicrobial Stewardship & Healthcare Epidemiology)
A β–lactam plus a macrolide or a respiratory fluoroquinolone alone is recommended as standard empiric antibacterial therapy for non-severe adults hospitalized with community-acquired pneumonia (CAP) per Infectious Diseases Society of America guidelines. However, the evidence in support of adding empiric atypical antibacterial therapy, and specifically the addition of a macrolide, is conflicting and should be balanced with additional factors: the necessity of covering atypical organisms, benefits of macrolide-associated immunomodulation, harms associated with antibiotic use, and selection for antibiotic-resistant organisms. In this review, we examine the role of atypical coverage in standard treatment regimens for patients admitted with non-severe CAP and specifically focus on the addition of macrolides to β–lactams. We conclude that a subset of patients should not be given atypical coverage as part of their regimen.